Public Service Quality of Hua Hin Municipality, Prachuap Khiri Khan Province - Yimlamai, Suthanya; Sartngern, Phachara (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2025)
This research article aims to 1) study the level of service quality of Hua Hin Municipality to the public, 2) Compare the relationship between personal characteristics and service quality of Hua Hin Municipality, 3) study the causal relationship between factors in service provision and the quality of service of Hua Hin Municipality to the public, and 4) study the guidelines for developing the quality of service of Hua Hin Municipality to the public. The research used mixed methods. The sample consisted of 400 community representatives living in Hua Hin Municipality. Use questionnaires as a tool for collecting data. The key informants were eight community leaders. In-depth interviews were used as the research tool. Data were analyzed using percentages, frequency distributions, means, standard deviations, multiple regression, and content analysis. The research results found that 1) The overall quality of public service of Hua Hin Municipality is at a high level, with an average value (𝑥̅= 3.88, S.D. = 0.65). 2) Different personal characteristics have different opinions on the quality of public service in Hua Hin Municipality. 3) Factors affecting the quality of service, service process, and service recipients’ expectations have a logical relationship with the quality of public service of Hua Hin Municipality with a statistical significance level of 0.001. Officers’ performance has a logical relationship with the quality of public service in Hua Hin Municipality, with a statistical significance level of 0.05. 4) The guidelines for developing the quality of public service in Hua Hin Municipality found that factors in the service, service process, service recipients’ expectations, and service personnel should be applied to develop the quality of service as follows: sufficient space and parking should be prepared; continuous training should be given to officers on service provision; officers should be ready to provide services to the public with willingness, enthusiasm, promptness, care, and attention dedication; and officers should be allocated with skills, knowledge, and abilities that are in line with their positions and duties.